Effects of anemia and peri-operative medication on wound healing in cleft lip and palate patients - Üstün, Galip Gencay; Menkü Özdemir, Fethiye Damla; Özgür, Figen (Acta Medica, 2024)
Introduction: Wound healing complications among cleft lip and palate patients pose risks of additional surgeries, reduced scar quality, and increased patient morbidity. This literature review aims to explore the impact of anemia and drug usage associated with respiratory complications, frequently encountered in these patients, on wound healing. Materials and Method: We conducted an extensive literature search without time constraints using PubMed and Google Scholar databases. The investigation into the effects of anemia and medications on wound healing was divided into three stages. The first stage examined the general effects of anemia and medications on wound healing. The second and final stages assessed wound healing in craniofacial and cleft lip/palate surgeries, respectively. Results: Preoperative anemia exerts no substantial influence on wound healing unless hemoglobin levels drop below 5 g/dl. No studies reported detrimental effects of glucocorticoids on wound healing. The impact of salbutamol use on wound healing remains controversial, while data regarding ipratropium usage are insufficient. Conclusion: Severe anemia is the only significant concern for wound healing, necessitating transfusion or improvement in anemia. It appears that short-term use of glucocorticoids after surgery does not have a negative effect on wound healing.It is worth noting that salbutamol and ipratropium usage may have detrimental effects, and while complete avoidance may not be feasible, their potential impact on wound healing should be considered.